Basic Concepts of Human Resource Management and Its Challenges in the Modern Era of Education - Dwi Nuriyah; Korinna Al Emira; Muazza; Aprillitzavivayarti (International Journal of Research in Education, 2026)
This study aims to analyze the basic concepts, functions, challenges, and strategies of human resource management in education in the modern era. This study uses a library research method with a descriptive-analytical approach, which examines various scientific literature, books, and journals published between 2015 and 2025 that are relevant to human resource management in education. The results of the study indicate that human resource management in educational institutions has evolved from an administrative function to a strategic function focused on developing teacher professionalism, digitizing work systems, and improving the welfare of educators. The main challenges identified include the acceleration of digital transformation, demands for teacher professionalism, and the need for global competencies balanced with moral and ethical values ​​in education. The conclusion of this study confirms that the success of educational institutions is highly dependent on the ability of human resource management to adapt to technological changes and globalization, while maintaining the humanistic dimension in the learning process. The urgency of this research lies in the importance of a sustainable transformation of HR management in education that is oriented towards strengthening teacher capacity so that they can face the dynamics of 21st-century education effectively and with dignity.